Pengembangan E-Modul Berbasis Pendekatan RME Menggunakan Kue Tradisional Bengkulu untuk Meningkatkan Kemampuan Pemecahan Masalah pada Materi Bangunan Datar Kelas IV SD - Endang Putriani; Agus Susanta; Irwan Koto (UNIB Press, 2023)
The purpose of this study is to determine the feasibility of material, language, design, student response, and product effectiveness resulting from the development of e-modules based on the RME approach using traditional Bengkulu cakes to improve problem solving skills in flat shape material for class IV SD. This research is a Research and Development (R&D) study. The model used in the development is the 4-D model. The subjects in the study were students of SDN 53 Kaur, which consisted of 12 students in class IV A as the control class, and 13 students in class IV B as the experimental class. The instruments used in this study were interview guideline, questionnaires, and problem-solving test questions in the form of essay for pretest and posttest. The data analysis technique used Aiken's V, Interrater Reliability, normality test, homogeneity test, t-test and N-gain score. From the research results it is known that the results of material, language, and design validation, as well as student responses to the use of e-modules are very feasible and well used in learning so that students are motivated to learn.